Recovering Ancient Grapevine Varieties: From Genetic Variability to In Vitro Conservation, A Case Study Variability to In Vitro Conservation, A Case Study - Gisbert, Carmina; Peiró, Rosa; San Pedro, Tania; Olmos, Antonio; Jiménez, Carles; García, Julio (INTECH, 2018)
A great number of varieties have been described in grapevine; however, few of them are currently in use. The increasing concern on varietal diversity loss has encouraged actions for recovering and preserving grapevine germplasm, which represents valuable resources for breeding as well as for diversification in grapevine-derived products. On the other hand, it is expected that this important crop, which is distributed in warm areas worldwide, will suffer the climate changes. Therefore, it is also convenient the identification of intravarietal variability and the recovery of accessions well adapted to particular environments. In this chapter, we will contribute to highlight the importance of recovering ancient materials, the usefulness of SSR markers to determine their molecular profile, the importance to analyze their virus status, and the possibilities that offer biotechnological tools for virus sanitation and in vitro storage as a complement of field preservation. In this context, we have evaluated different grapevine accessions and developed in vitro culture protocols for micropropagation, sanitation, and storage grapevine cultivars. In this work, we report the results obtained for the historic variety “Valencí Blanc” (or “Beba”) and the historic and endangered variety “Esclafagerres” (“Esclafacherres” or “Esclafacherris”).